2008
DOI: 10.1080/14786430802477976
|View full text |Cite
|
Sign up to set email alerts
|

An atomic mechanism for the boson peak in metallic glasses

Abstract: The boson peak in metallic glasses is modeled in terms of local structural shear rearrangements. Using Eshelby's solution of the corresponding elasticity theory problem (J. D. Eshelby, Proc. Roy. Soc. A241, 376 (1957)), one can calculate the saddle point energy of such a structural rearrangement. The neighbourhood of the saddle point gives rise to soft resonant vibrational modes. One can calculate their density, their kinetic energy, their fourth order potential term and their coupling to longitudinal and tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
1
19
0
1
Order By: Relevance
“…c N will tend to increase with N , because a larger number of atoms or molecules offers more structural rearrangement possibilities 11 . N should be decidedly larger than six, because a recent boson peak investigation 19 in terms of the Eshelby picture showed that the barrier in the case of six atoms or spherical molecules is still close to zero, the elastic restoring forces from the outside being of the same order as the ones from the inside. The partition function…”
Section: The Modelmentioning
confidence: 99%
“…c N will tend to increase with N , because a larger number of atoms or molecules offers more structural rearrangement possibilities 11 . N should be decidedly larger than six, because a recent boson peak investigation 19 in terms of the Eshelby picture showed that the barrier in the case of six atoms or spherical molecules is still close to zero, the elastic restoring forces from the outside being of the same order as the ones from the inside. The partition function…”
Section: The Modelmentioning
confidence: 99%
“…From dielectric loss spectroscopy the variety of relaxation processes in glasses is well known [1]. The assignment of microscopic processes to contributions of the loss spectrum is still a matter of debate [2]. It is commonly agreed that the low frequency loss part (a peak) is the signature of viscous loss and by this linked to the glass transition.…”
Section: Introductionmentioning
confidence: 99%
“…1͒ in description of glass transition and nonpropagating relaxation processes in supercooled liquids and glasses 2,3 much less attention was paid to theoretical studies on dispersion of collective excitations in glass systems. There are many qualitative theoretical explanations of specific features of dispersion and damping of acoustic excitations in glasses and emergence of a lowfrequency excess on the density of vibrational states ͑boson peak͒, [4][5][6][7][8] while numerical studies of collective excitations in glasses are mainly performed by oversimplified fit procedures or by instantaneous mode analysis within harmonic approximation. Moreover there exist several points of view on the origin of the boson peak.…”
Section: Introductionmentioning
confidence: 99%